COMPOSITION OF LIGHT HYDROCARBONS IN JURASSIC TIGHT OILS IN THE CENTRAL SICHUAN BASIN, CHINA: ORIGIN AND SOURCE ROCK CORRELATION. (24th March 2022) - Lu, Xiaolin; Li, Meijun; Wei, Tengqiang; Wu, Changjiang; Tang, Youjun; Wang, Xiaojuan; Hong, Haitao; Liu, Yuan; Ran, Zichao
Abstract : Crude oil reserves in tight Middle and Lower Jurassic reservoirs are of increasing exploration interest in the central Sichuan Basin, SW China. However, the origin of these "tight oils" is poorly understood. In this study, sixteen samples of light oils/condensates from tight Middle and Lower Jurassic reservoir rocks were analysed using gas chromatography (GC) and isotope ratio mass spectrometry to investigate the oils' origin and to classify them into genetic families. The tight oils can be divided into two families. Family I oils occur in the Gongshanmiao oilfield where reservoir units comprise the Da'anzhai Member of the Lower Jurassic Ziliujing Formation, the Lower Jurassic Lianggaoshan Formation, and the First Member of the Middle Jurassic Shaximiao Formation. Family I oils are characterized by relatively low values of the methylcyclohexane (MCH) and cyclohexane (CH) indexes, low values of Mango's parameter K2 for light hydrocarbon composition, and relatively negative δ 13 C values ranging from ‐30.8‰ to ‐28.9‰. Family I oils are inferred to be self‐sourced by lacustrine shales in the Da'anzhai Member and the Lianggaoshan Formation in the study area, both of which are rich in sapropelic organic matter. These source rocks also charged reservoirs in the First Member of the Shaximiao Formation. By contrast, the newly discovered Family II oils, which occur at the Jinhua oilfield and the as‐yet undeveloped Qiulin and Bajiaochang structures, are reservoired in the Second Member of Shaximiao Formation. Family II oils have higher values of the MCH index, CH index and Mango's K2 parameter, and δ 13 C values varying from ‐27.5‰ to ‐25.4‰. These oils have similar light hydrocarbon compositions and δ 13 C values to oils derived from source rocks in the Upper Triassic Xujiahe Formation which contain dominantly humic organic matter. Family II oils are therefore inferred to be derived from the coaly mudstones in the Xujiahe Formation. The different compositions of the tight oils in the First and Second Members of the Shaximiao Formation appear to be controlled by the distribution and thickness of source rocks in the study area. Thus, the Gongshanmiao oilfield where Family I oils occur in the First Member is close to the depocentre of source rocks in the Da'anzhai Member and Lianggaoshan Formation. These source rocks are inferred to have charged the First Member reservoirs which may also be present in nearby oil‐ and gas‐bearing structures such as Nanchong and Yingshan. By contrast, Family II oils occur in tight reservoirs in the Second Member in areas with thick successions of Upper Triassic Xujiahe Formation mudstone source rocks, such as the Jinhua oilfield. In areas where both source rocks are present such as the Zhongtaishan and Lianchi oilfields, Shaximiao Formation reservoirs appear to contain both Family I and Family II oils.